Penerapan Prinsip Mudharabah dalam Akuntansi Syariah: pada PT Bank Syariah - Rahmat HIdaya; Kheyra Al Zaphira; Bias Puspa Pitaloka Dewa Brata; Peny Cahaya Azwari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
PT Bank Syariah's use of mudharabah concepts in Islamic accounting is examined in this paper. An agreement for profit sharing between the fund manager (mudharib) and the fund owner (shahibul maal) is known as mudharabah. The purpose of this research is to investigate how well mudharabah concepts align with the National Sharia Council's Fatwa and PSAK No. 105. The results show that PT Bank Syariah has applied mudharabah accounting principles in accordance with PSAK 105 in measuring, recognizing, presenting, and disclosing mudharabah financing transactions. However, the implementation of mudharabah pillars and conditions has not fully complied with the Fatwa of the National Sharia Council. Transaction recording uses the completion date method and cash recognition. Mudharabah investments are presented at their carrying value. Nevertheless, the portion of mudharabah financing is still smaller compared to murabahah contracts. This study concludes that PT Bank Syariah needs to improve the conformity of mudharabah principles with the Fatwa of the National Sharia Council.